Delayed Care and Mortality Among Women and Men With Myocardial Infarction. Issue 8 (August 2017) - Bugiardini, Raffaele; Ricci, Beatrice; Cenko, Edina; Vasiljevic, Zorana; Kedev, Sasko; Davidovic, Goran; Zdravkovic, Marija; Miličić, Davor; Dilic, Mirza; Manfrini, Olivia; Koller, Akos; Badimon, Lina
Abstract : Background: Women with ST‐segment–elevation myocardial infarction (STEMI) have higher mortality rates than men. We investigated whether sex‐related differences in timely access to care among STEMI patients may be a factor associated with excess risk of early mortality in women. Methods and Results: We identified 6022 STEMI patients who had information on time of symptom onset to time of hospital presentation at 41 hospitals participating in the ISACS‐TC (International Survey of Acute Coronary Syndromes in Transitional Countries) registry (NCT01218776) from October 2010 through April 2016. Patients were stratified into time‐delay cohorts. We estimated the 30‐day risk of all‐cause mortality in each cohort. Despite similar delays in seeking care, the overall time from symptom onset to hospital presentation was longer for women than men (median: 270 minutes [range: 130–776] versus 240 minutes [range: 120–600]). After adjustment for baseline variables, female sex was independently associated with greater risk of 30‐day mortality (odds ratio: 1.58; 95% confidence interval, 1.27–1.97). Sex differences in mortality following STEMI were no longer observed for patients having delays from symptom onset to hospital presentation of ≤1 hour (odds ratio: 0.77; 95% confidence interval, 0.29–2.02). Conclusions: Sex difference in mortality following STEMI persists and appears to be driven by prehospital delays in hospital presentation. Women appear to be more vulnerable to prolonged untreated ischemia. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT01218776.